2007
DOI: 10.1158/1055-9965.epi-07-0480
|View full text |Cite
|
Sign up to set email alerts
|

An International Case-Control Study of Interleukin-4Rα, Interleukin-13, and Cyclooxygenase-2 Polymorphisms and Glioblastoma Risk

Abstract: Previous studies found that allergies are inversely related to risk of glioma. In an earlier publication, using data from a Swedish case-control study, Schwartzbaum et al. report an inverse relation between risk of glioblastoma and four single nucleotide polymorphisms (SNP) on two genes [interleukin (IL)-4Ra, IL-13] that are associated with allergies. In addition, recent studies suggest that IL-4 and IL-13 induce cyclooxygenase-2 (COX-2) to resolve brain inflammation. To see whether previous Swedish results (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
(36 reference statements)
2
41
2
Order By: Relevance
“…Stronger support for a protective association with asthma is suggested by one study reporting that, compared with controls, cases were less likely to carry polymorphisms in the IL4RA and IL13 genes that increase the risk for asthma and more likely to carry polymorphisms that decrease the risk for asthma (11). However, these findings were not replicated when the authors repeated their analysis in a larger pooled data set (12), and Turner et al (22) were unable to show differences in brain tumor mortality among a cohort of asthma and hay fever suffers in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger support for a protective association with asthma is suggested by one study reporting that, compared with controls, cases were less likely to carry polymorphisms in the IL4RA and IL13 genes that increase the risk for asthma and more likely to carry polymorphisms that decrease the risk for asthma (11). However, these findings were not replicated when the authors repeated their analysis in a larger pooled data set (12), and Turner et al (22) were unable to show differences in brain tumor mortality among a cohort of asthma and hay fever suffers in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies suggest a lower risk for gliomas among people reporting a history of allergies and asthma (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Schwartzbaum et al (11) reported that asthma susceptibility gene polymorphisms in IL4RA and IL13 were associated with a decreased risk for adult gliomas; however, they were unable to show significance in a larger analysis (12). Another report suggested a reduced risk for glioma with the use of nonsteroidal antiinflammatory drugs (NSAID; ref.…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of nine population-based studies failed to establish NOCs as a causal agent for glioma. 85 PBTs molecular epidemiologic studies with focus on inflammation An inverse association between IL-4RA, IL-13, and glioblastoma was observed and the relationship was not affected by allergic conditions (Table 4 [86][87][88][89][90][91][92] ). The studies also provide evidence to establish allergies as a risk factor for glioma and thus urge the identification of more candidate genes to be studied under this category.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Metabolismmentioning
confidence: 99%
“…Trials concerning the role of the IL-13 -1112 C/T polymorphism in cancer development were performed in an Iranian population, but neither in lung cancer nor breast cancer, there was no association observed Sameni et al, 2009). The similar trials were performed on a mixed population in patients with glioma, but there was also no connection indicated between the IL-13 -1112 C/T polymorphic variants and cancer occurrence (Schwartzbaum et al, 2007).…”
Section: Discussionmentioning
confidence: 99%